Occurrence, distribution and risk assessment of organophosphate esters (OPEs) in water sources from Northeast to Southeast China. (15th August 2022) - Zhu, Kongrui; Sarvajayakesavalu, Suriyanarayanan; Han, Yingnan; Zhang, Haifeng; Gao, Junmin; Li, Xinyan; Ma, Mei
Abstract: With the wide utilization of organophosphate esters (OPEs) in recent years, OPEs have been detected more frequently in the aquatic environment. However, the distribution of OPEs in drinking source water has rarely been investigated across a large region. In this study, the occurrence and distribution of 13 OPEs were investigated in 23 source water sites from Northeast to Southeast (spacing greater than 3320 km) with a direct injection ultra-performance liquid chromatography-tandem mass spectrometry (UPLC–MS/MS) method. Total OPEs ranged from 218.8 to 636.6 ng/L, with a mean of 380.8 ng/L. The average detected concentration of OPEs in southern cities was higher than that in northern cities. Chlorinated OPEs accounted for 64.74% of the total concentration. Triethyl phosphate (TEP), tri (2-chloroethyl) phosphate (TCEP), and tri (chloropropyl) phosphate (TCPP) were detected in all water samples. Rainfall is a significant factor that affects the OPE concentration (less rainfall, higher concentration). China's OPE concentrations have rapidly reached a median level when compared to those of other countries. Ecological risk assessment showed that most OPEs have no or low risk to organisms (fish, crustacea, algae), except tricresyl phosphate (TCP), which is medium risk. The risk of OPEs in less-rain regions needs to be of greater concern, especially TCP. Graphical abstract: Image 1 Highlights: Chlorinated OPEs and alkyl OPEs were the main OPEs in Chinese water sources. Precipitation is a significant factor that affects the OPEs concentration. TCEP increases with the precipitation raise, while other OPEs are inverse. TCP poses a medium risk to the fish, algae, and crustacea.